Preparation and Characterization of Nanoparticles Made from Co-Incubation of SOD and Glucose - Liping Cai; Chuntong Lin; Nannan Yang; Zhijie Huang; Song Miao; Xiaochao Chen; Jianru Pan; Pingfan Rao; Shutao Liu (Nanomaterials, 2017)
The attractive potential of natural superoxide dismutase (SOD) in the fields of medicine and functional food is limited by its short half-life in circulation and poor permeability across the cell membrane. The nanoparticle form of SOD might overcome these limitations. However, most preparative methods have disadvantages, such as complicated operation, a variety of reagents—some of them even highly toxic—and low encapsulation efficiency or low release rate. The aim of this study is to present a simple and green approach for the preparation of SOD nanoparticles (NPs) by means of co-incubation of Cu/Zn SOD with glucose. This method was designed to prepare nanoscale aggregates based on the possible inhibitory effect of Maillard reaction on heating-induced aggregation during the co-incubation. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) results indicated that the Maillard reaction occurred during the co-incubation process. It was found that enzymatically active NPs of Cu/Zn SOD were simultaneously generated during the reaction, with an average particle size of 175.86 ± 0.71 nm, and a Zeta potential of −17.27 ± 0.59 mV, as established by the measurement of enzymatic activity, observations using field emission scanning electron microscope, and analysis of dynamic light scattering, respectively. The preparative conditions for the SOD NPs were optimized by response surface design to increase SOD activity 20.43 fold. These SOD NPs showed storage stability for 25 days and better cell uptake efficacy than natural SOD. Therefore, these NPs of SOD are expected to be a potential drug candidate or functional food factor. To our knowledge, this is the first report on the preparation of nanoparticles possessing the bioactivity of the graft component protein, using the simple and green approach of co-incubation with glucose, which occurs frequently in the food industry during thermal processing.